World on a wire [videorecording (DVD)] - Fassbinder, Rainer Werner, 1945-1982; Löwitsch, Klaus, 1936-2002; Valentin, Barbara, 1940-2002; Rabben, Mascha; Galouye, Daniel F. (Criterion collection, 2012)
The noir-spiked tale of a reluctant action hero, a cybernetics engineer who uncovers a massive corporate conspiracy substituting simulations for reality.